2011
DOI: 10.4317/medoral.16.e23
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and post-antifungal effects of chlorhexidine, fluconazole, chitosan and its combinations on Candida albicans

Abstract: Objective: The aim of this work was to assess the antifungal and post-antifungal effects of chlorhexidine, fluconazole, chitosan and its combinations on virulence factors of Candida albicans. Study Design: Ten isolated strains of Candida albicans obtained from 10 patients with oral candidiasis and a collection strain of C. albicans were treated with antifungal agents in different concentrations or combinations of them. Virulence factors analyzed were the cell surface hydrophobicity, the germinative tube develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…Chlorhexidine gluconate 0.2% (Glaxo Smith Kline, Brentford, UK) was dissolved in sterile phosphate‐buffered saline (PBS) at pH 7.2 and was prepared as 0.005%, 0.0025% and 0.00125% solutions immediately prior to each experiment as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorhexidine gluconate 0.2% (Glaxo Smith Kline, Brentford, UK) was dissolved in sterile phosphate‐buffered saline (PBS) at pH 7.2 and was prepared as 0.005%, 0.0025% and 0.00125% solutions immediately prior to each experiment as previously described …”
Section: Methodsmentioning
confidence: 99%
“…In addition, a recent study has shown that subtherapeutic levels of CG are also effective in suppressing germ tube (GT) formation of oral C. albicans isolates obtained from healthy as well as diabetics, asthmatics using steroid inhalers and smokers . Furthermore, it has been shown that CG alone or in combination with other antimycotic agents were capable of inducing a PAFE as well as modulating virulent attributes of Candida including phospholipase production . For these reasons, oral rinses containing CG may be an appropriate substitute to conventional antimycotics in the management of oral candidosis …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the current study indicates that the antifungal activity of amphotericin B may probably be realized even when administered at extended intervals due to the PAFE elicited by this drug. However, since the PAFE depends upon the organism in question, the concentration, exposure time and mode of action of the tested drug and other environmental factors [11,16,17,18], further studies with a larger battery of organisms are needed to determine the relationship between the PAFE of amphotericin B and its dosage regimen applicable in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-fungal activity if Chitosan is through permeabilization of yeast cells and efflux of potassium ions, along with an increased uptake of calcium ions, and inhibition of respiration, fermentation, and viability of the cells. [17] A study [18] was done to assess the antifungal and post-antifungal effects of chlorhexidine, fluconazole, chitosan and its combinations on Candida albicans in patients with OM and chitosan was found to be effective to inhibit the concentrations of Candida. Chitosan is a bio-adhesive or a mucoadhesive polymer and forms an occlusive dressing over the mucosa which inhibits the settling of secondary infection and also aids in the protection of the wound from secondary injuries.…”
Section: Discussionmentioning
confidence: 99%